The Prospects of Lactobacillus oris as a Potential Probiotic With Cholesterol-Reducing Property From Mother's Milk - Afrin, Sadia; Akter, Suraiya; Begum, Shamima; Hossain, Md Nur (Frontiers in Nutrition, 2021)
This experiment was conducted to characterize potential Lactobacillus spp. isolated from mother’s milk and infant feces to obtain new and specific probiotic strains. In this study, seven ascendant strains were identified as Lactobacillus spp. based on their morphological characteristics and biochemical properties. Among them, only one (C-1) isolate was identified as Lactobacillus oris through BioLogTM identification and investigated probiotic potentiality tests such as pH and bile tolerance, NaCl tolerance test, gastric juice tolerance, antioxidant activity, resistance to hydrogen, reduction of sodium nitrate, antimicrobial activity and antibiotic susceptibility test. The result showed that the strain is a potential probiotic based on their probiotic capability. The identified strain was found most acid-tolerant retained around 80% viability for up to 4 h at pH 1.0 and 2.0. The isolate showed tolerance against up to 1.50% bile concentration and gastric juice and able to grow 1 - 6% NaCl concentrations. Lactobacillus oris showed resistance to most of the antibiotics as well as antagonistic activity against the tested pathogen, good antioxidant properties, reduction of sodium nitrate and H2O2. The isolate exhibited good intestinal epithelial adhesion properties and SDS page was performed for secreted protein analysis. Moreover, the strain showed promising cholesterol-lowering properties based on the cholesterol level. This present result stated that L. oris has superior probiotic properties and regarded as a potential probiotic candidate.